Peripheral blood biomarkers of early immune reconstitution in newly diagnosed multiple myeloma. Issue 3 (13th December 2018) - Binder, Moritz; Rajkumar, S. Vincent; Lacy, Martha Q.; Gertz, Morie A.; Buadi, Francis K.; Dispenzieri, Angela; Hwa, Yi L.; Fonder, Amie; Hobbs, Miriam; Hayman, Suzanne R.; Zeldenrust, Steven R.; Lust, John A.; et al.
Abstract: Peripheral blood biomarkers of tumor microenvironment and immune surveillance are independent prognostic factors in multiple myeloma. The timing and prognostic impact of immune reconstitution has been studied after autologous hematopoietic stem cell transplantation, less is known about its significance in newly diagnosed multiple myeloma. We studied absolute lymphocyte (ALC) and absolute monocyte (AMC) counts at the time of treatment initiation and 1 month thereafter in 771 newly diagnosed patients. Two hundred and thirty‐four patients (31%) had evidence of immune dysregulation at baseline (abnormal biomarkers). Eighty‐seven of these patients (37%) recovered normal biomarkers at 1 month (early immune reconstitution). The absence of immune dysregulation at baseline (compared to the presence thereof) was associated with better overall survival (HR 0.77, 95% CI 0.61‐0.97, P  = 0.025, n = 771). The absence of immune dysregulation at 1 month (compared to the persistence or development thereof) was associated with better overall survival (HR 0.63, 95% CI 0.50‐0.80, P  < 0.001, n = 771). Early immune reconstitution (compared to the persistence or development of immune dysregulation) was associated with better overall survival (HR 0.62, 95% CI 0.43‐0.92, P  = 0.016, n = 771). Cytogenetic high‐risk disease was negatively, and treatment with immunomodulators positively, associated with early immune reconstitution. The presence or development of immune dysregulation in newly diagnosed multiple myeloma is an independent risk factor. The favorable impact of early immune reconstitution suggests immune dysregulation to be a potentially modifiable risk factor that may be exploited for therapeutic benefit.